An Exploration of How the Resourcing of Staff and Book Purchasing Affects the Development of China's Public School Libraries in Guangzhou. Issue 1 (2nd January 2020) - Zhang, Wenyan; Ji, Mengmeng; Wang, Hui; Zhang, Chenglong; Xu, Sheng; Wu, Yejun; Song, Fei
ABSTRACT: School libraries provide invaluable support to national education systems of China. The current status of school libraries in China is generally far from being able to meet the demands of students and teachers. This study explores the factors that prevent the development of public school libraries in Guangzhou, China. A questionnaire and four sets of interview questions were designed to explore the factors which hinder the development of school libraries in 12 districts of Guangzhou. 132 valid responses were collected from primary and middle schools in Guangzhou. School libraries call for considerable improvements, especially from the views of teachers. This research found that lack of sufficient funds and professional personnel prevents school libraries from providing professional information services.